The effect of drying temperatures on morphological and chemical properties of dried chestnut flours - Correia, Paula (2013)
The effect of drying conditions on morphological and chemical properties of two Portuguese Castanea sativa varieties (Longal and Martainha) was evaluated. All chestnut drying curves were found to be different according to drying temperatures (40 C, 50 C, 60 C and 70 C). Those conditions also affected both chemical composition of flours and morphological properties of starch. Colour parameters of the flours (L* c*h ) generally decreased with increasing drying temperature, total colour difference (TCD*) also significantly changed for samples dried at different tested conditions. The drying temperature seems to affect starch morphology, with Longal starch granules always somewhat smaller. The results showed that the higher the drying temperature, the higher the reducing sugars content and the lower the starch content. In what concerns differences among the studied varieties, it can be stated that Longal presents whiter flours, higher reducing sugars content, lower starch and sucrose contents. In opposition, Martainha flours presented lower percentage of amylose and damaged starch. From the results it can be concluded that the marked effects that drying temperature exerted on the characteristics and properties of chestnut flours are different in both varieties studied